2017
DOI: 10.1016/j.homp.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Individualized homeopathic treatment in addition to conventional treatment in type II diabetic patients in Hong Kong – a retrospective cohort study

Abstract: Individualized homeopathic treatment was associated with better glycaemic control compared with standard conventional treatment alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…14 In a retrospective cohort study, 27 patients were treated by IHMs together with conventional care, which showed better glycemic control in comparison with the historical data from 40 diabetic patients receiving conventional care only. 26 Early research also suggested that combining homeopathic treatment with anti-diabetic medicines might result in better outcomes than conventional treatment alone. 27 Recently, one single-group, feasibility study on pre-diabetic individuals showed improvement of serological markers in 88% of cases under constitutional homeopathic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In a retrospective cohort study, 27 patients were treated by IHMs together with conventional care, which showed better glycemic control in comparison with the historical data from 40 diabetic patients receiving conventional care only. 26 Early research also suggested that combining homeopathic treatment with anti-diabetic medicines might result in better outcomes than conventional treatment alone. 27 Recently, one single-group, feasibility study on pre-diabetic individuals showed improvement of serological markers in 88% of cases under constitutional homeopathic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recently, one single-group, feasibility study on pre-diabetic individuals showed improvement of serological markers in 88% of cases under constitutional homeopathic treatment. 26 Several remedies have been recommended in the homeopathy literature for treating diabetes, including Argentum metallicum , Arsenicum album , Plumbum metallicum , Sulphur , Cuprum metallicum , China officinalis , Kreosotum and Lachesis mutus . 28 Some of these, for example Arsenicum album , Sulphur and Lachesis mutus , were also prescribed in this trial of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In India, around 30% of households use the traditional system of medicine [ 11 ], and more than 25% of AYUSH (an acronym for Ayurveda, Yoga and naturopathy, Unani, Siddha, and Homeopathy) users prefer homoeopathy [ 12 ]. Homoeopathy is among the commonest used CAM for DM and its complications [ 8 , 13 , 14 ]. Studies have reported that 1.5% of DM patients in India avail of homoeopathic treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few researchers doubted the existence of scientific evidence of the efficacy of homoeopathy in DM [ 16 ] though other researchers have refuted their claims [ 17 ]. Research on managing DM and its complication showed significantly positive results in favour of homoeopathy [ 14 , [18] , [19] , [20] , [21] ]. Most studies have focused on evaluating the effect of either specific homoeopathic remedies or complex remedies in DM [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation